Antimicrobial Resistanceamong Intensive Care Unit Patients in A Tertiary Care Hospital of Bangladesh (Bangladesh Journal of Medicine, 2021)
Background: Antimicrobial resistance is a growing concern specially among the critically ill patients who are often treated by multiple antibiotics. But, the data regarding the pattern of antimicrobial resistance in this population are often insufficient.Objective: To observe the pattern of antimicrobial resistance among the patients admitted into the intensive care unit (ICU).Methodology: This prospective observational study was carried out in the ICU of a tertiary care hospital of Bangladesh over 6 months. Samples of blood, urine, tracheal aspirate, wound swab and pus were obtained from the patients, cultured and analyzed.Results: Among 100 subjects, the most common primary diagnoses were aspiration pneumonia (29%) and urinary tract infection (UTI) (24%). Out of 315 samples, microorganisms were isolated from 125 samples (39.68%). The most common sample yielding positive culture was tracheal aspirate (67.2%), and the most frequently isolated microorganisms were Pseudomonas spp. (35%), Escherichia coli (28%), Acinetobacterspp. (24%) andKlebsiellaspp. (18%). Acinetobacterspp., Pseudomonasspp. and Klebsiellaspp.were the commonest resistant organisms. Overall prevalence of resistance to antibiotics were: ceftriaxone 72%, ceftazidime 78.4%, ciprofloxacin 81.6%, gentamicin 84%, meropenem 49.6% andnetilmicin 39.2%. Meropenem was the most sensitive antibiotic against Klebsiellaspp.(66.67%) but Acinetobacterspp.was still resistant to meropenem and amikacin but sensitive to cotrimoxazole (66.67%). Multidrug resistant Pseudomonas, Acinetobacter and, Klebsiella species were found; piperacillin-tazobactam combination showed